(untitled) (Marketing Journal, 2026)
Abstract The article examined the expanding role of the digital economy in strengthening production efficiency within industrial enterprises of the Republic of Uzbekistan. The study traced the progressive trajectory of digital economic development from 2018 to 2023, identified key institutional and infrastructural achievements that accelerated digital transformation, and assessed the promising opportunities for broader adoption of digital technologies across productive sectors. The analysis demonstrated a consistent upward trend in the contribution of the digital economy to aggregate output and documented substantial improvements in ICT infrastructure, e-governance capacity, and enterprise-level digital adoption. The findings confirmed that Uzbekistan has established a robust institutional foundation for sustained digital economic growth, with expanding internet access, a strengthening regulatory environment, and an increasingly digitally skilled workforce positioning the country favorably for continued advancement. Keywords: digital economy, industrial enterprises, production efficiency, ICT development, e-governance, Uzbekistan